Development strategy of Keraton Museum as the center of cultural tourism destination in Sumenep District - Wahdah, Nikmatul Bahril; Nabila, Ilsa; Suharto, Bambang; Isnaini, Santi (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
This study aims to develop a development strategy for the Sumenep Palace Museum as a cultural tourism des-tination in Sumenep Regency. The research approach uses qualitative case studies, SWOT analysis, IFAS/EFAS matrix and TOWS matrix preparation. Data collection was carried out by interviewing museum managers and local communities, as well as observing the location of the Sumenep Palace Museum. Tourism Sumenep Pal-ace Museum has a historical building that is still maintained, but public facilities still need to be improved. People are still highly interested in the Palace Museum, and the threat is losing competitiveness with other tours, so people are bored visiting the museum. It is found that the Sumenep Palace Museum is located in quadrant 1, which is an aggressive strategy, meaning that it has the potential for development. The devel-opment strategy that can be applied is to collaborate with artists/culturalists, education institution, and young people to enliven the museum by holding art/cultural performances regularly and maximizing the role of so-cial media with influencers in promoting Sumenep Palace Museum tourism.